Meconopsis (sect. Impeditae) Grey-Wilson, Gen. ... - Elvebakk, Arve; Bjerke, Jarle W. (Zenodo, 2024)
4.3.Meconopsis sect. ImpeditaeGrey-Wilson, Gen. Meconopsis: 46. 2014 Type species. Meconopsis impedita Prain. Notes. Section Impeditae Grey-Wilson (Grey-Wilson 2014) partly overlaps with section Forrestianae as monographed later by Yoshida and Sun (2019 a) and referred to above. Two new species of Impeditae, M. angustipetala W. T. Wang and M. brachynema W. T. Wang, were described from China (Wang 2019). ... : Published as part of Elvebakk, Arve & Bjerke, Jarle W., 2024, Papaver recircumscribed: A review of neighbouring Papaveraceae genera, including Afropapaver nom. et stat. nov. and Oreomecon, a large, Arctic-Alpine genus, pp. 105-188 in PhytoKeys 248 on pages 105-188, DOI: 10.3897/phytokeys.248.121011 ...